IABSE Conference, Nara 2015: Elegance in Structures 2015
DOI: 10.2749/222137815815774629
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic behaviour of the roof interventions in the Basilica San Francesco in Assisi

Abstract: <p>During the 1997 Umbria-Marche earthquake, two of the vaults of the Basilica of San Francesco in Assisi collapsed as a result of two earthquakes with 5.6 and 5.8 magnitudes. The structure had endured stronger earthquakes for centuries before these events, and there are likely many reasons for the 1997 collapse, such as damages cumulated from previous earthquakes or the retrofitting made to the structure over its lifetime. A full description and history of the different retrofit interventions of the Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
0
0
Order By: Relevance
“…To consider the impact of embedment in the perimeter walls and stiff abutment, the model was truncated at the base. The failure of the vaults began at a somewhat higher level, as various studies of the damage to historic buildings during seismic events have shown, as was noted in [6], effectively being embedded into support parts to offset the outward thrust [28], [29]. Thus, this approximation is frequently used in the literature to understand and forecast how masonry vaults would react to seismic activity.…”
Section: Physical Modelmentioning
confidence: 99%
“…To consider the impact of embedment in the perimeter walls and stiff abutment, the model was truncated at the base. The failure of the vaults began at a somewhat higher level, as various studies of the damage to historic buildings during seismic events have shown, as was noted in [6], effectively being embedded into support parts to offset the outward thrust [28], [29]. Thus, this approximation is frequently used in the literature to understand and forecast how masonry vaults would react to seismic activity.…”
Section: Physical Modelmentioning
confidence: 99%
“…Studying damage of historic buildings in seismic events reveals that failure of vaults does not initiate at their springings, but at the key-stone zone which is essentially embedded into support elements to counteract the outward thrust [37], [38], [39]. Examples are displayed in Figure 1.…”
Section: The Vault Modelmentioning
confidence: 99%